Pengenalan Makanan Khas Kota Surabaya Melalui Media Buku Ilustrasi sebagai Upaya Pelestarian Budaya Lokal - Aulia Lillah Violita; Aris Sutejo; Widyasari Widyasari (Pusat Riset dan Inovasi Nasional, 2026)
Surabaya is one of Indonesia's metropolitan cities with a rich culinary heritage characterized by distinctive flavors and high cultural value. However, with the passage of time and the influence of globalization, traditional Surabaya cuisine has become less familiar, especially among the younger generation. This study aims to reintroduce Surabaya's signature dishes through illustrated books as an effort to preserve local culture. The methods used include literature study, field observation, and interviews with sources related to Surabaya cuisine. The result is an illustrated book that features various traditional foods such as rujak cingur, lontong balap, tahu tek, sate kelapa, and semanggi, presented in an attractive and informative visual format. Through this illustrated book, it is hoped that readers will not only learn about the diversity of Surabaya's cuisine, but also understand the cultural values contained within it, thereby fostering a sense of pride and awareness to preserve the local culinary heritage.